Tracing the cosmological origin of gas that fuels in situ star formation in TNG50 galaxies - Wittig, Ole; Ramesh, Rahul; Nelson, Dylan (Astronomy and astrophysics, 2025)
Based on their cosmological origin, the stars of a galaxy can be divided into two categories: those that enter through merger events (ex situ) and those born in the main progenitor (in situ). We used the TNG50 cosmological magnetohydrodynamical simulation and its Lagrangian tracer particles to explore and quantify the origin of gas that ultimately forms the in situ stars of galaxies. We tracked back the baryonic mass contributing to the z = 0 in situ stellar populations of galaxies, studying trends in mass from dwarfs to group-scale halos. We find that more massive halos acquire this matter earlier than lower-mass halos, reflecting an overall earlier assembly of their in situ stellar mass. Defining the Lagrangian half-mass radius RL, 1/2 of a galaxy as the distance containing half of the mass that will form its in situ stars by z = 0, we find that RL, 1/2 is larger for more massive halos at early times, reflecting larger “in situ Lagrangian regions”. However, the dependence of this radius on halo mass becomes flat at z ≃ 3 and then inverts toward z = 0. In addition, RL, 1/2 increases rapidly with redshift, surpassing the virial radii of halos at z ∼ 2. This marks the cosmic epoch at which most of the gas that eventually forms the in situ stars of galaxies leaves the intergalactic medium (IGM) and enters halos, a transition that occurs earlier for more massive halos. The formation redshift of the in situ stellar component increases with halo mass, while the formation redshift of the dark matter halo decreases, indicative of a differential assembly history between these two components. Finally, we decomposed the z = 0 in situ stellar mass into its distinct modes of accretion. Smooth accretion from the IGM is the most important for low-mass galaxies, while mergers and satellite-stripped gas become relevant and even dominant only for high-mass galaxies.